Computational investigation on CO2 adsorption in titanium carbide-derived carbons with residual titanium. (January 2017) - Zhang, Difan; Dutzer, Michael R.; Liang, Tao; Fonseca, Alexandre F.; Wu, Ying; Walton, Krista S.; Sholl, David S.; Farmahini, Amir H.; Bhatia, Suresh K.; Sinnott, Susan B.
Abstract: We develop a new approach for modeling titanium carbide derived-carbon (TiC-CDC) systems with residual titanium by the generation of modified atomistic structures based on a silicon carbide derived-carbon (SiC-CDC) model and the application of weighted combinations of these structures. In our approach, the original SiC-CDC structure is modified by (i) removing carbon, (ii) adding carbon and (iii) adding titanium. The new atomic scale carbide-derived carbon (CDC) structures are investigated using classical molecular dynamics simulations, and their pure CO2 adsorption isotherms are calculated using grand canonical Monte Carlo simulations. The system of TiC-CDC with residual titanium is modeled as weighted combinations of pure carbon CDC structures, CDC structures with titanium and a TiC crystalline structure. Our modeling is able to produce both structural properties and adsorption isotherms in accordance with experimental data. The fraction of different models in the systems successfully reflects the structural differences in various experimental TiC-CDC samples. The modeling also suggests that in partially etched TiC-CDC systems, the titanium that may be accessible to CO2 gas at the transitional interface may provide significant interaction sites for CO2 and may lead to more efficient overall gas adsorption. Graphical abstract: